2019
DOI: 10.3390/ijerph16091496
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Physical Activity and Sedentary Behaviors with Upper Respiratory Tract Infections and Sleep Duration in Preschool Children—Study Protocol

Abstract: Currently, there is no consensus regarding the benefits of physical activity in terms of upper respiratory tract infections (URTIs) among different age groups of children. The number of school students avoiding physical education is on the rise. Children of all ages spend more time on sedentary behavior, eat less nutritious food and spend less time sleeping. All of these concomitant aspects adversely affect the immune system. A coexisting problem of a growing society is a large number of URTIs which is the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…Secondly, upper respiratory tract infection symptoms, (e.g., running nose, sneezing and feeling tired) may overlap with the symptomatology of allergic rhinitis and could have been misreported in our self-assessed questionnaire, which is another limitation. Nevertheless, the WURSS-k questionnaire was validated for such cases, also in our preliminary study [ 16 ]. Thirdly, although greater overcrowding and poorer housing quality might pose an increased risk of allergy symptoms and coincide with URTS caused by air pollution becoming a limitation of this study, Samoliński et al demonstrated that, in Poland, impoverished housing standards do not indicate higher risk of sensitization and house dust mite allergy [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, upper respiratory tract infection symptoms, (e.g., running nose, sneezing and feeling tired) may overlap with the symptomatology of allergic rhinitis and could have been misreported in our self-assessed questionnaire, which is another limitation. Nevertheless, the WURSS-k questionnaire was validated for such cases, also in our preliminary study [ 16 ]. Thirdly, although greater overcrowding and poorer housing quality might pose an increased risk of allergy symptoms and coincide with URTS caused by air pollution becoming a limitation of this study, Samoliński et al demonstrated that, in Poland, impoverished housing standards do not indicate higher risk of sensitization and house dust mite allergy [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data on respiratory morbidity were collected using a self-reported questionnaire based on the polish version of the Wisconsin Upper Respiratory Symptom Survey for kids (WURSS-k) [ 16 ]. The research tool for collecting data on children’s health was a self-filling questionnaire carried out with the CAWI (computer-assisted web interviewing) technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper respiratory tract infections (URTIs) are the most common cause of outpatient clinic visits among patients of all age groups [ 1 , 2 ], accounting for more than 50% of pediatric medical consultations, and causing massive clinical and economic burden [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, almost all studies focused on children's own environmental exposure, lifestyle factors, and health condition, such as family members' interaction, sleep environment, physical activity, obesity, etc. [8][9][10][11][12] Data from the ALSPAC cohort in the UK indicated that maternal mood disturbance in pregnancy has persisting effects on sleep problems in their children. 13 A very recent study in Finland also suggested that maternal depressive symptoms during pregnancy are associated with an increased risk of children's sleep deficiency and sleep disorders.…”
Section: Introductionmentioning
confidence: 99%